Implementation of Quantum Teaching Learning Model to Improve Learning Outcomes and Students’ Mind Mapping in Al-Islam Subject - Yumidiana Tya Nugraheni; Agus Firmansyah (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
This research aimed to determine the application of the Quantum Teaching learning model to improve learning outcomes and the ability to make mind mapping in Al-Islam. This article is the result of a classroom action research in Muhammadiyah Elementary School, Condongcatur, Yogyakarta with observations, tests, interviews, and documentation as data collection methods. Based on the results of reflection, the teacher carries out a follow-up plan, which can compose revisions of the old or new plan. The application of learning using Quantum Teaching on Al-Islam material with a small discussion model, mind mapping, interactive lectures and problem solving is quite effective in the process of learning activities in the classroom. This can be seen from the results of research, among others: can improve student learning outcomes and making mind mapping material Al-Islam. Quantum Teaching Model can encourage teachers to develop themselves in the learning process. Quantum Teaching Model gained 10 points in cycle I, which means the learning process started to be seen. Cycle II the learning process got 14 points. In cycle I the result of the average student learning outcomes was 94 and the making of an average mind mapping was 92. In cycle II student learning outcomes were 99 on average and mind mapping was 96.